2020
DOI: 10.1186/s43067-020-00023-6
|View full text |Cite
|
Sign up to set email alerts
|

Economic emission dispatch on unit commitment-based microgrid system considering wind and load uncertainty using hybrid MGWOSCACSA

Abstract: Economic emission dispatch (EED) of a three-unit stand-alone microgrid system supported by a wind farm is percolated in this paper. The adverse effects of stochastic and uncertainty nature of wind energy in raising the generation cost of the microgrid system are studied in this article. Unit commitment (UC) of the generating units is taken into account which helps in reducing the generation cost and provides relaxation time to the generation units. Three cases are contemplated for the study. For the first two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…The Multi-Objective Grey Wolf Optimizer (MOGWO) can find the Pareto optimal front of any shape. Finally, the result of a complex real-world Multi-Objective OPF (MOOPF) problem validates that the MOGWO algorithm can solve any kind of non-linear and complex problem with many constraints in unknown search space [17]- [19]. Meanwhile, special emphasis is being paid to incorporating renewable energy supplies into the grid to decarbonize the electric power system.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…The Multi-Objective Grey Wolf Optimizer (MOGWO) can find the Pareto optimal front of any shape. Finally, the result of a complex real-world Multi-Objective OPF (MOOPF) problem validates that the MOGWO algorithm can solve any kind of non-linear and complex problem with many constraints in unknown search space [17]- [19]. Meanwhile, special emphasis is being paid to incorporating renewable energy supplies into the grid to decarbonize the electric power system.…”
Section: Introductionmentioning
confidence: 84%
“…𝑝 𝑤 (𝑣) = { 𝑝 𝑤𝑟 , for 𝑣 𝑟 < 𝑣 ≤ 𝑣 𝑜𝑢𝑡 0, for 𝑣 < 𝑣 𝑖𝑛 and 𝑣 > 𝑣 𝑜𝑢𝑡 𝑝 𝑤𝑟 ( 𝑣 − 𝑣 𝑖𝑛 𝑣 𝑟 − 𝑣 𝑖𝑛 ) , for 𝑣 𝑖𝑛 ≤ 𝑣 ≤ 𝑣 𝑟 (18) where, 𝑣 𝑜𝑢𝑡 , 𝑣 𝑟 , and 𝑣 𝑖𝑛 , denotes the cut-out, rated, and cutin speed of the wind turbine, respectively and 𝑝 𝑤𝑟 signifies the rated generated power of the turbine. ) , for 𝐺 ≥ 𝑅 𝑐 (19) where, 𝑅 𝑐 denotes a particular irradiance position set as 120 W m 2 ⁄ , 𝐺 𝑠𝑡𝑑 denotes the solar irradiation in the typical environment fixed at 1000 W 𝑚 2 ⁄ , and the PV unit's rated performance is 𝑃 𝑠𝑟 . The flow rate of water (𝑄 𝑤 ) and effective pressure head (𝐻 𝑤 ) are calculated by the output of a small hydro plant.…”
Section: H Power Models Of Solar Pv Wind and Hybrid Plantsmentioning
confidence: 99%
“…Yanpeng et al [18] have suggest internet of things (IoT) built micro grid allowed smart structures to reach digital then automatic in reneswable side [19] have developed micro grid is a small grid which gives power for the small areas or local areas like village and commercial place. Dey et al [20] have suggested to avoid transmission losses and uninterrupted energy flow micro system is used and renewable energy sources remain recycled for reducing the emission of harmful gaseous. Phung et al [21] suggested in PV system will requires the efficient management and monitoring the movements of the panel for absorption of radiation.…”
Section: Renewable Sources With Optimization Algorithmsmentioning
confidence: 99%
“…A modified harmony search (MHS) algorithm is proposed to solve the combined economic emission dispatch (CEED) problem of the microgrid taking into account the solar and wind power cost functions [14]. A novel hybrid algorithm consisting of grey wolf optimizer, sine-cosine algorithm and crow search algorithm has been implemented for economic dispatch of a three-unit stand-alone microgrid supported by wind energy [15]. Weirong Liu et al [16] proposed a cooperative reinforcement algorithm for distributed economic dispatch in microgrids.…”
Section: Introductionmentioning
confidence: 99%